Leslie Burrowes A Young Dancer in Dresden and London, 1930-34 - Nicholas, Larraine (Edinburgh: Edinburgh University Press, 2010)
RESUMEN: Leslie Burrowes (1908-1985) was the first British dancer to receive the full diploma of the Wigman School in Dresden and subsequently became Wigman's official UK representative. The letters she wrote to her benefactor, Dorothy Elmhirst, with the addition of my commentary and annotations, provide a lens through which to view the School as she experienced it. Her return to London brought her into a quite different cultural environment. I argue that she energetically launched her career, performing and teaching in her new style and contesting what she considered to be false charges against modern dance. But it appears that, by the end of this period, she had adjusted her expectations, away from solo theatrical recitals (in the Wigman mode) and more towards the education of children and students, and a small-scale but intense programme centred on her home studio.